Core Vocabulary: Its Morphological Content and Presence in Exemplar Texts. Issue 1 (4th April 2017) - Hiebert, Elfrieda H.; Goodwin, Amanda P.; Cervetti, Gina N.
Abstract: This study addresses the distribution of words in texts at different points of schooling. The first aim was to identify a core vocabulary that accounts for the majority of the words in texts through the lens of morphological families. Results showed that 2, 451 morphological families, averaging 4.61 members, make up the core vocabulary of school texts. The 11, 298 words in the 2, 451 morphological families account for 58% of the approximately 19, 500 most frequent words in written English. The majority of the morphological families appear by the end of the elementary school period (85%), but a small group of morphological families (15%) is added through the middle to high school period. Analyses of the ranks of words across grade bands indicated that late‐appearing words gain in prominence in higher level texts as some elementary‐level words become less frequent. The second aim of the study was to determine the degree to which the core vocabulary accounted for the words in an independent but critical set of texts: the exemplar texts identified within the Common Core State Standards. The 2, 451 families accounted for 97.1% (grades K and 1) to 89.1% (grade 11 through college) of the total words in texts and 95.6% (grades K and 1) to 74.9% (grade 11 through college) of the unique words in texts. Implications of the findings on the nature and role of the core vocabulary in complex texts are suggested for researchers, curriculum developers, and publishers.